BRAFV600E immunohistochemistry in conjunction with mismatch repair status predicts survival in patients with colorectal cancer - Toon, Christopher W (Nature Publishing Group, 2014)
Immunohistochemistry has recently been validated for the detection of the BRAFV600E mutation across a range of tumor types. In colorectal carcinoma, the presence of the BRAFV600E mutation can be used to virtually exclude Lynch syndrome in mismatch repair-deficient tumors. In mismatch repair-proficient tumors, BRAFV600E mutation assessed by molecular methods has been proposed as a poor prognostic factor. We investigated whether combined BRAFV600E and mismatch repair status assessment by immunohistochemistry alone can be used as a prognostic marker in the routine clinical setting. We performed immunohistochemistry for BRAFV600E, MLH1, PMS2, MSH2, and MSH6 on 1426 consecutive unselected colorectal carcinomas. Ninety-one (6.4%) carcinomas were mismatch repair-proficient and BRAFV600E mutant, and these tumors demonstrated a significantly worse 5-year survival of 49.7% compared with mismatch repair-proficient BRAF wild type (74.1% of tumors, 65.4% survival), mismatch repair-deficient BRAFV600E mutant (12.9% of tumors, 70.1% survival), and mismatch repair-deficient BRAF wild type (6.6% of tumors, 73.6% survival). The poor survival was confirmed by univariate analysis (P<0.01) but fell away in multivariate analysis (P=0.68) because of the strong effect of tumor stage and age on overall survival. We conclude that in addition to its utility in screening for Lynch syndrome, reflex BRAFV600E and mismatch repair assessment by immunohistochemistry can be used as a powerful predictor of all-cause survival.